The use of TPGS in drug delivery systems to overcome biological barriers. (5th January 2021) - Tavares Luiz, Marcela; Delello Di Filippo, Leonardo; Carolina Alves, Renata; Sousa Araújo, Victor Hugo; Lobato Duarte, Jonatas; Maldonado Marchetti, Juliana; Chorilli, Marlus
Graphical abstract: Highlights: Overcoming biological barriers is a challenge for nanomedicines. TPGS covering nanomedicines can improve permeation through biological barriers. TPGS blocks P-glycoprotein efflux pump and reduces multidrug resistance mechanism. Abstract: Nanotechnology has been applied in the medicine field to improve the treatment of a wide range of diseases. However, to reach the nanomedicines delivery to desirable target tissue for promote an enhancement of pharmacological activity, these nanomedicines must overcome biological barriers, such as mucus gel, skin, corneal and blood–brain barriers. Aiming the increase nanomedicines permeation through these barriers, surface modifications of nanocarriers with permeation enhancers and/or specific ligands for cellular receptors have been widely investigated. Among these modifications, d-α-Tocopheryl polyethylene glycol 1000 succinate (TPGS) is a biocompatible macromolecule that has been evaluated as a permeation enhancer. TPGS is a non-ionic surfactant composed by the natural vitamin E bonded with polyethylene glycol 1000 (PEG) and its composition have been responsible to enhance cellular internalization and permeation of nanomedicines through biological barriers. In addition, this molecule has acted as solubilizer, emulsifier, stabilizer and P-glycoprotein (P-gp) inhibitor, that are important features to manufacture nanomedicines with suitable to overcome barriers and multidrug resistance (MDR) mechanisms. This review will address the TPGS physicochemical and biological features and its most recent application in nanomedicine field to overcome biological barriers.